Edukasi Literasi Keuangan Terkait Tabungan dan Dana Pensiun pada UMKM Arum Manis di Dusun Kemloko, Mojokerto - Yuniarsih, Nia; Andrew, Richard; Gago, Monica Sylviana (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Financial literacy is important for MSME actors to manage and develop their businesses easily. The financial management carried out by Arum Manis MSMEs is still very simple, by not separating between their own capital and business capital. This community service activity aims to educate and assist the owners and employees of Arum Manis MSMEs about savings and pension funds. The method used a qualitative method with primary data sources by distributing questionnaires to owners and employees of Arum Manis MSMEs. Descriptive analysis is used to explain and analyze the achievement of the percentage of respondents who answered yes and no. The results of community service activities include (a) 14% of respondents have savings and atm (b) 100% of respondents believe they can support their families until old age and have investments in the form of land and houses (c) 100% of respondents have never heard of a pension fund program and have no desire to have a pension fund program. These community service activity results show that owners and employees have sufficient knowledge about savings but no desire to have a pension fund.